2018
DOI: 10.1111/febs.14408
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the apo cAMP‐binding domain of HCN4 – a stepping stone toward understanding the cAMP‐dependent modulation of the hyperpolarization‐activated cyclic‐nucleotide‐gated ion channels

Abstract: The hyperpolarization-activated cyclic-nucleotide-gated (HCN) ion channels control nerve impulse transmission and cardiac pacemaker activity. The modulation by cAMP is critical for the regulatory function of HCN in both neurons and cardiomyocytes, but the underlying mechanism is not fully understood. Here, we show how the structure of the apo cAMPbinding domain of the HCN4 isoform has contributed to a model for the cAMP-dependent modulation of the HCN ion-channel. This model recapitulates the structural and dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…1 d), which interconvert in the fast exchange regime, as previously shown (15). cAMP-binding selects and stabilizes the active state (26,39), whereas cAMP analogs modulate the position of the autoinhibitory versus active P 1 5 P 2 equilibrium. Such modulations correlate with the cNMP-dependent changes in activation voltages (DV 1/2 ) measured by electrophysiology for integral full-length ion channels (15).…”
Section: Introductionsupporting
confidence: 59%
“…1 d), which interconvert in the fast exchange regime, as previously shown (15). cAMP-binding selects and stabilizes the active state (26,39), whereas cAMP analogs modulate the position of the autoinhibitory versus active P 1 5 P 2 equilibrium. Such modulations correlate with the cNMP-dependent changes in activation voltages (DV 1/2 ) measured by electrophysiology for integral full-length ion channels (15).…”
Section: Introductionsupporting
confidence: 59%
“…In small dorsal root ganglia neurons, PGE 2 -evoked activation of HCN-mediated current and depolarization of resting membrane potential via EP 3 (Sachs et al., 2009) is inhibited by activation of GPR35, a Gi/o-coupled receptor that reduces intracellular cAMP levels (Resta et al., 2016). It is known that cAMP can bind to the cyclic nucleotide-binding domain of the HCN3 (Akimoto et al., 2018) and activate it (Robichaux and Cheng, 2018). In our preliminary study, we have found that PD reduces the expression of catalytic subunit of protein kinase A in oxytocin neurons (Li et al., unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…EPACs also regulate several physiological mechanisms including cellular secretion, adhesion and differentiation [ 22 ]. Finally, the cAMP binding domain has been identified at cyclic nucleotide-gated ion channels; cAMP-mediated channels’ stimulation remains of paramount importance for neuronal impulse transmission and cardiomyocyte contractility [ 29 ].…”
Section: Camp Signalingmentioning
confidence: 99%